Polyaniline-Acetylene black-Copper cobaltite based ternary hybrid material with enhanced electrochemical properties and its use in supercapacitor electrodes - Das T.; Verma B. (My University, 2025)
A new system based on Polyaniline-Acetylene black-Copper cobaltite composite has been prepared and affirmed by XRD, UV, SEM, FTIR, and EDS characterizations. The rod-like texture of ternary hybrid system offered excellent electrochemical activity in comparison to single and binary systems. CV and CD results revealed outstanding redox behavior of the ternary hybrid electrodes. Ternary electrode (PACC) presented the highest specific capacitance value of 690 F/g at 1 mA/cm2 current density. PACC electrode based symmetric supercapacitor had a specific capacitance of 137.25 Fg-1 at 1 mA/cm2 of current density. PACC symmetric supercapacitor had the highest specific power and specific energy of 3308.85 W.kg-1 and 19.064 Wh.kg-1, respectively. The ternary system provides less charge transfer resistance values compared to all other systems. Thermal stability of the ternary composite is way better than polyaniline, which is due to the contribution of copper cobaltite and acetylene black. The overwhelming characteristics of the ternary hybrid composite bring it to the limelight as an excellent candidate in the field of supercapacitors. © 2019 John Wiley & Sons, Ltd.